Germinação in vitro e micropropagação de baru (Dipteryx alata Vogel) - Oliveira, Thaís Alves (2023)
The work aimed to evaluate the in vitro germination of baru seeds in different sucrose concentrations and the effect of the growth regulator BAP on the induction of shoots in in vitro multiplication. For in vitro germination, seeds were submerged in sodium hypochlorite for disinfestation at four different times (0, 5, 10 and 20 minutes) and inoculated in WPM medium with different sucrose concentrations (0, 15 and 30 g L-1), evaluating germination percentages, contamination percentage, germination velocity index (GVI) and mean germination time (MT). For the in vitro multiplication experiment, apical segments from the germination of baru seeds were used and submitted to different concentrations of growth regulator (BAP), being: 0; 1; 1.5; 2 and 4 mg L-1 and at concentrations of 0; 1.5; 3; 6 and 9 mg L-1 for the in vitro multiplication experiment with apical segments from shoots obtained through the first subcultivation. In the in vitro germination, treatments T2 (S0 x HS5) and T3 (S0 x HS10) presented 90% germination at day 8 and 100% germination at day 14, with superior result for IVG (1.28) in absence of sucrose in the culture medium. The concentrations of 4 mg L-1 (93.75%) and 6 mg L-1 (96.87%), proved to be more promising for the sprouting of the explants to occur, because when there is an increase in the concentration of BAP in 9 mg L-1 (90.62%) the culture medium causes toxicity and inhibition of the multiplication of the baru sprouts to the explant.